Efficacy and safety of guanabenz acetate treatment for non-alcoholic fatty liver disease: a study protocol for a randomised investigator-initiated phase IIa study. Issue 7 (12th July 2022) - Iwaki, Michihiro; Kessoku, Takaomi; Tanaka, Kosuke; Ozaki, Anna; Kasai, Yuki; Yamamoto, Atsushi; Takahashi, Kota; Kobayashi, Takashi; Nogami, Asako; Honda, Yasushi; Ogawa, Yuji; Imajo, Kento; et al.
Abstract : Introduction: Non-alcoholic fatty liver disease (NAFLD) is a metabolic syndrome phenotype in the liver and thus obviously associated with metabolic abnormalities, including insulin resistance-related to hyperglycaemic and hyperlipidaemia. The prevalence of NAFLD is increasing worldwide. However, currently, there is no consensus regarding the efficacy and safety of drugs used to treat patients with NAFLD/non-alcoholic steatohepatitis (NASH). Guanabenz acetate, a selective α2-adrenoceptor stimulator used in the treatment of hypertension, binds at a high-affinity constant to a nuclear transcriptional coregulator, helicase with zinc finger 2 (Helz2) and inhibits Helz2-medaited steatosis in the liver; chronic oral administration of guanabenz acetate produces a dose-dependent inhibition of lipid accumulation by inhibiting lipogenesis and activating fatty acid Β-oxidation in the liver of obese mice, resulting in improvement of insulin resistance and hyperlipidaemia. Taken all together, guanabenz acetate has a potentially effective in improving the development of NAFLD/NASH and metabolic abnormalities. In this randomised, open label, parallel-group, phase IIa study, we made attempts to conduct a proof-of-concept assessment by evaluating the efficacy and safety of guanabenz acetate treatment in patients with NAFLD/NASH. Methods and analysis: A total of 28 adult patients with NAFLD or NASH and hypertension complications meeting the inclusion/exclusion criteria will be enrolled. Patients will be randomised to receive either 4 or 8 mg guanabenz acetate (n=14 per group). Blood tests and MRI will be performed 16 weeks after commencement of treatment. The primary endpoint will be the percentage reduction in hepatic fat content (%) measured using MRI-proton density fat fraction from baseline by at least 3.46% at week 16 after treatment initiation. Ethics and dissemination: Ethics approval was obtained from the Ethics Committee of Yokohama City University Hospital before participant enrolment (YCU021001). The results of this study will be submitted for publication in international peer-reviewed journals, and the key findings will be presented at international scientific conferences. Participants wishing to know the results of this study will be contacted directly on data publication. Trial registration number: This trial is registered with ClinicalTrials.gov (number: NCT05084404 ). Protocol version: V.1.1, 19 August 2021.